PEMILIHAN MATERIAL KONTSRUKSI BANGUNAN PERUMAHAN MENGGUNAKAN METODE ANALISIS HIRARKI PROSES - Neneng Winarsih; Firda Ainun Nisah; Siti Halimah; Nadia Ayudya Adikirana (Universitas Islam Nahdlatul Ulama Jepara, 2023)
THE SELECTION OF RESIDENTIAL BUILDING CONSTRUCTION MATERIALS USING ANALYTICAL HIERARCHY PROCESS METHODSThe selection of building materials is important in the planning process of housing construction because it will affect the quality of the building and the determination of the selling price of a building. so that an appropriate method is needed in making decisions to determine the specifications of the material to be used. The purpose of this study is to obtain efficient building materials both in terms of price and quality. so that they can support the concept of housing. The concept of housing buildings in this study uses a minimalist concept. The material limitations that will be determined in this study are materials for roof coverings, floor coverings, ceilings, window sills, and doors. The material selection process uses a analysis hierarchy process method with material selection criteria including price, specifications, design, and durability. Each criterion uses three alternatives as a comparison. Data collection was obtained through experts in a housing company with an expert as the head of the planning division. The results of data processing were obtained for the roof covering materials using concrete tiles, floor coverings using granite, ceilings using kalsiboard, window sills using aluminum, and doors using the solid wood material. This research is expected to be useful, especially for construction business actors in determining building materials.Â